2019
DOI: 10.1063/1.5123800
|View full text |Cite|
|
Sign up to set email alerts
|

Semiclassical analysis of the quantum instanton approximation

Abstract: We explore the relation between the quantum and semiclassical instanton approximations for the reaction rate constant. From the quantum instanton expression, we analyze the contributions to the rate constant in terms of minimum-action paths and find that two such paths dominate the expression. For symmetric barriers, these two paths join together to describe the semiclassical instanton periodic orbit. However, for asymmetric barriers, one of the two paths takes an unphysically low energy and dominates the expr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 60 publications
1
35
0
Order By: Relevance
“…Nonetheless, a good understanding of the instanton paths has helped in the development of a number of methods based on path-integral sampling which are applicable to reactions in solution. 61,62,104 We hope that the information obtained on the instanton in this work will help derive novel path-integral-based rate theories which can describe the inverted regime more rigorously.…”
Section: Discussionmentioning
confidence: 94%
“…Nonetheless, a good understanding of the instanton paths has helped in the development of a number of methods based on path-integral sampling which are applicable to reactions in solution. 61,62,104 We hope that the information obtained on the instanton in this work will help derive novel path-integral-based rate theories which can describe the inverted regime more rigorously.…”
Section: Discussionmentioning
confidence: 94%
“…The resulting expressions only involve time-independent quantities, which can be evaluated by sampling imaginary time paths. Recently, Vaillant et al 48 have suggested a slight modification of the original adiabatic quantum instanton, which they have called the projected quantum instanton (PQI). This enforces sampling of paths close to the semiclassical instanton and results in an expression that is even more closely related to Wolynes theory.…”
Section: Introductionmentioning
confidence: 99%
“…The transition state theory (TST) proposed around 1930s was the first attempt for a balance between accuracy and efficiency [10,11]. At the same time, some of its approximate semi-empirical revisions can also capture the quantum effects in the reaction, such as quantum transient theory [8,12], but those methods still have many non-negligible shortcomings. The TST method assumes that there is a dividing surface separating the reactants and products, so it ignores the recrossing in dynamical effects, and it is also difficult to find an accurate dividing surface, especially for high-dimensional or barrier-less reactions.…”
Section: Introductionmentioning
confidence: 99%